Rebel - Weber, David, 1952-; Fox, Richard, 1978- (Weber, David, 1952- Ascent to empire., 2024)
"HE NEVER WANTED TO BE A REBEL The Five Hundred, the elite families who rule the Terran Federation, control its political power and its wealth, and they've grown steadily wealthier and more powerful, thanks to the war against the Terran League. War may be hard on the people who get caught in its path, but it's very good for business, in the short term, and the Five Hundred own the shipyards that build the Navy's ships. They own virtually all the industry that produces the weapons and matériel the war consumes so voraciously . . . and they've made damn sure someone else does the dying. True, there are a few flies in the Five Hundred's ointment. There's the growing hatred and resentment of the Fringe Worlds, whose children do eighty percent of the dying in the Five Hundred's war. But the Five Hundred have made sure the Fringe knows what will happen to any system that goes "out of compliance." There are the lunatic conspiracy nuts who insist that the alien Rishathan Sphere is secretly aiding the League's military, but the Five Hundred have forced them to keep their mouths shut where it matters. And then there's Terrence Murphy, a man of honor who loves the Federation, who springs from the Five Hundred, yet knows it for what it is and is determined to speak for its victims. But the five hundred have dispatched ample force to deal with him and his handful of lunatic followers. Unfortunately, the Fringe has paid enough of its children's lives, and it no longer cares what may happen if it dares to defy the Five Hundred. Worse, the lunatic conspiracy nuts were right, and the Rish have planned carefully for the Federation's destruction. And, worst of all, the Five Hundred have fatally underestimated Terrence Murphy"--